Alterations in the lipid profile associate with a dysregulated inflammatory, prothrombotic, anti-fibrinolytic state and development of severe acute kidney injury in coronavirus disease 2019 (COVID-19): A study from Cincinnati, USA. Issue 3 (May 2021) - Henry, Brandon M.; Szergyuk, Ivan; de Oliveira, Maria Helena Santos; Abosamak, Mohammed Fawzi; Benoit, Stefanie W.; Benoit, Justin L.; Lippi, Giuseppe
Abstract: Background and aims: Reduction of atherogenic lipoproteins is often the ultimate goal of nutritional interventions, however this is complicated given that hypolipidemia is frequently observed in coronavirus disease 2019 (COVID-19) patients. We aimed to explore the association of hypolipidemia with patient outcomes in terms of immunothrombosis and multiorgan injury, focusing on specialized apolipoproteins apo A1 and apo B. Methods: Lipid profiles of 50 COVID-19 patients and 30 sick controls presenting to the Emergency Department (ED) were measured in this prospective observational study. The primary outcome was development of severe acute kidney injury (AKI). Need for hospitalization and ICU admission were secondary outcomes. Lipoproteins were analyzed for independent association with serum creatinine (SCr) increase ratio and correlated with a wide panel of biomarkers. Results: COVID-19 cohort had significantly lower apo A1 (p = 0.006), and higher apo B/apo A1 ratio (p = 0.041). Patients developing severe AKI had significantly lower LDL-C (p = 0.021). Apo B/apo A1 was associated with 2.25-fold decrease in serum SCr increase ratio, while LDL-C with a 1.5% decrease. Hypolipidemia correlated with low plasminogen, ADAMTS13 activity/VWF:Ag, and high inflammatory biomarkers (CRP, IL-6, IL-8, IL-10), plasminogen activator inhibitor-1 (PAI-1), ED creatinine, and SCr increase ratio. Conclusion: Although favored in dietetics, findings of a low LDL-C in COVID-19 patients should be alarming in light of our observations. Low apo B/apo A1 ratio and LDL-C are predictive of renal deterioration in COVID-19 patients, and low LDL-C in particular may potentially serve to indicate COVID-19 related AKI driven by disrupted fibrinolysis and a secondary thrombotic microangiopathy-like process. Highlights: Hypolipidemia is seen in COVID-19 patients developing severe AKI. Low apo B/apo A1 ratio and LDL-C may indicate COVID-19 related renal deterioration. Hypolipidemia is associated with a dysregulated immune system and hypofibrinolysis. Correlation of LDL-C with ADAMTS13/VWF supports a secondary TMA driving AKI.